Boosting Women Academics’ Professional Development during the Global Pandemic: Problems and Solutions - Risa Fitria; Ani Pujiastuti; Grace Amialia Neolaka; Maria Yus Trinity Irsan (Prodi PGSD FIP UNM, 2021)
ABSTRACTThe activity aims to understand women academics practices to develop their professional career during the Covid-19. Female lecturers from different areas in Indonesia were invited to join the forum group discussion virtually held through a webinar on August 31, 2020. The activity began with a session delivered by a keynote speaker regarding the issues and challenges that female academics dealt with in higher education, particularly amidst Covid-19. The speaker elaborated several factors such as social and organizational cultures that have influenced women’s professional development when working remotely. The webinar received positive reception and feedback from the participants. It was concluded that even though the issues cannot be immediately addressed, positive encouragement and support from women to women are highly recommended. Keywords: Female Academics; Professional Development; Pandemic.